Dear America letters home from Vietnam - Home Box Office; Couturie Company; Vietnam Veterans Ensemble Theater Co. ([New York Ambrose Video Pub., 1987)
A history of American involvement in the Vietnamese conflict told through letters of American soldiers and illustrated with news footage, home movies and still photos.
VHS.
Keywords: Vietnamese Conflict, 1961-1975 -- Personal narratives, American